Peran Mahasiswa Kuliah Kerja Nyata dan Transformasi Digital UMKM dengan Pengaktifan UMKM di Google Maps Desa Selayang - Fhakir Nur Al Fidha; Mutia Dila Puspita; Nina Puspita; Salwa Latipah; Rahmad Efendi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Selayang Village is one of the villages in Selesai District where most of the residents have micro, small, and medium enterprises (MSMEs) as the main source of livelihood. However, until now, MSME actors in the village still face limited knowledge and skills in utilizing digital technology, especially in the field of marketing. Most business actors still rely on conventional marketing methods, such as word-of-mouth promotion, which has an impact on limited market reach. Through this community service activity, it is hoped that MSMEs will be able to optimize digital marketing so that their marketing area becomes wider and more competitive. This service aims to assist and assist the community in registering the location of MSMEs and public facilities on the Google Maps platform. The method of implementing the service includes the stages of socialization, technical assistance, and direct MSME registration. The results of the activity showed that as many as nine MSMEs were successfully registered and their business profiles were optimized through a door-to-door approach. All business actors responded positively because they now have a digital footprint that makes it easier for consumers to find business locations. Thus, this activity is expected to increase business visibility, the competitiveness of MSMEs, and the welfare of the people of Selayang Village